How do you combine \frac { w } { 5} root3(-64) + root3{ 512w ^ { 3 } } / { 5} - \frac { 2} { 5} \sqrt { 50w } - 4\sqrt { 2w } into a single term, if possible?

1 Answer
Jun 30, 2017

w/5root(3)(-64)+root(3)(512w^3)/5-2/5sqrt(50w)-4sqrt(2w)=(4w)/5-6sqrt(2w)

Explanation:

w/5root(3)(-64)+root(3)(512w^3)/5-2/5sqrt(50w)-4sqrt(2w)

= w/5root(3)((-4)xx(-4)xx(-4))+root(3)(8wxx8wxx8w)/5-2/5sqrt(5xx5xx2w)-4sqrt(2w)

= w/5xx(-4)+(8w)/5-2/5xx5xxsqrt(2w)-4sqrt(2w)

= -(4w)/5+(8w)/5-2/cancel5xxcancel5xxsqrt(2w)-4sqrt(2w)

= (4w)/5-6sqrt(2w)